2006
DOI: 10.1007/s10725-006-9149-8
|View full text |Cite
|
Sign up to set email alerts
|

Butenolide from plant-derived smoke enhances germination and seedling growth of arable weed species

Abstract: We tested the applicability of the recently identified major germination cue from smoke (a butenolide 3-methyl-2Hfuro[2,3-c]pyran-2-one) on 18 weed species from non-fire prone environments. For the study species we compared the relative effectiveness of alternating temperatures, KNO 3 , GA 3 , smoke water and the butenolide on germination percentage, germination rate and seedling mass. We found that while smoke stimulated germination in a number of species it also had negative impacts on other species. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 26 publications
6
88
1
6
Order By: Relevance
“…Butenolide was a very active dormancy breaking factor at very low concentrations (10 -8 M) and could remove completely or partially deep dormancy in seeds at 15-25°C. Fully dormant seeds of A. fatua were more sensitive to butenolide than partially dormant seeds from the United Kingdom (Daws et al 2007) and Australia (Stevens et al 2007). Similar effects of smoke-water and butenolide on seed germination were observed in experiments with Asteraceae (Merritt et al 2006) and some agricultural plants (Daws et al 2007;Stevens et al 2007).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Butenolide was a very active dormancy breaking factor at very low concentrations (10 -8 M) and could remove completely or partially deep dormancy in seeds at 15-25°C. Fully dormant seeds of A. fatua were more sensitive to butenolide than partially dormant seeds from the United Kingdom (Daws et al 2007) and Australia (Stevens et al 2007). Similar effects of smoke-water and butenolide on seed germination were observed in experiments with Asteraceae (Merritt et al 2006) and some agricultural plants (Daws et al 2007;Stevens et al 2007).…”
Section: Discussionsupporting
confidence: 56%
“…Stevens et al (2007) observed that both smoke-water and butenolide stimulated germination of freshly harvested but only partially that of dormant seeds of A. fatua from Australia. In another study, smoke-water inhibited germination but butenolide only partially stimulated germination of dry stored A. fatua seeds collected in the United Kingdom (Daws et al 2007).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Since the identification of KAR 1 , several diverse species have been classified as responding positively to karrikins. These include the arable weeds Brassica tournefortii and Sisymbrium orientale (Brassicacaeae) (Stevens et al 2007), and Avena fatua and Sorghum halepense (Poaceae) (Daws et al 2007). A recent study of the effects of smokewater and KAR 1 on seed germination of 13 species from South China identified only one (Aristolochia debilis; Aristolochiaceae) as responding positively to 1 nM KAR 1 or more (Zhou et al 2014).…”
Section: Seed Germination Responses To Karrikinsmentioning
confidence: 99%